Sugar transporters and their molecular tradeoffs during abiotic stress responses in plants. Issue 2 (4th March 2022) - Salvi, Prafull; Agarrwal, Ruchi; Kajal,; Gandass, Nishu; Manna, Mrinalini; Kaur, Harmeet; Deshmukh, Rupesh
Abstract: Sugars as photosynthates are well known as energy providers and as building blocks of various structural components of plant cells, tissues and organs. Additionally, as a part of various sugar signaling pathways, they interact with other cellular machinery and influence many important cellular decisions in plants. Sugar signaling is further reliant on the differential distribution of sugars throughout the plant system. The distribution of sugars from source to sink tissues or within organelles of plant cells is a highly regulated process facilitated by various sugar transporters located in plasma membranes and organelle membranes, respectively. Sugar distribution, as well as signaling, is impacted during unfavorable environments such as extreme temperatures, salt, nutrient scarcity, or drought. Here, we have discussed the mechanism of sugar transport via various types of sugar transporters as well as their differential response during environmental stress exposure. The functional involvement of sugar transporters in plant's abiotic stress tolerance is also discussed. Besides, we have also highlighted the challenges in engineering sugar transporter proteins as well as the undeciphered modules associated with sugar transporters in plants. Thus, this review provides a comprehensive discussion on the role and regulation of sugar transporters during abiotic stresses and enables us to target the candidate sugar transporter(s) for crop improvement to develop climate‐resilient crops.